ANALYSIS OF IDEAS ON THE PHENOMENON OF THE “SOCIALLY ACTIVE INDIVIDUAL” IN THE SPIRITUAL HERITAGE OF SA'DEDDIN HAMAWI (World Conference on Social Sciences, Law and Public Policy, 2026)
Reinterpreting the views on the socially active individual within Sufi philosophy holds paramount relevance in modern scientific and philosophical discourse. During contemporary eras of globalization, spiritual crisis, and existential uncertainty, the socio-moral potential of Sufism serves as a crucial foundation for fostering individual responsibility, moral resilience, and social altruism. The paradigm of Sufi engagement liberates the human personality from egoism and utilitarianism, elevating it to the level of a perfect human being who comprehends their duty toward society and nature. Accordingly, the socially active individual in Sufi philosophy is not merely an isolated mystic focused on personal spiritual perfection, but a constructive and creative agent who enriches existence, builds society, and reforms socio-moral relations through knowledge and ethics. This paper systematically examines the ontological, epistemological, and ethical foundations of social activity in the teachings of the 13th-century Kubrawi master Sa’deddin Hamawi, alongside the development of these concepts in the works of his disciple Aziz al-Din Nasafi.
Keywords: Sufism, Sa’deddin Hamawi, Kubrawiya, socially active individual, Perfect Human (al-Insan al-Kamil), sainthood (walayah), spiritual journey (sayr wa suluk), futuwwa, Aziz al-Din Nasafi.